The influence of corporate characteristics and Good Corporate Governance toward the risk management disclosure; La influencia de las características corporativas y el buen gobierno corporativo hacia la divulgación de la gestión de riesgos - Einde Evana; Ade Widiyanti; Yenni Agustina; Raida Fuadi; Edwin Mirfazli; Leire San-Jose (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
This research study aims to obtain empirical evidence to the influence of company characteristics (firm size, profitability, leverage and liquidity) and good corporate governance (audit committee, board size, and public ownership structure) toward the risk management disclosure. This research study uses the Index of Enterprise Risk Management (IERM) as the parameter of risk management disclosure. This research study uses secondary data, the population of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) in 2013-2015. The sampling technique was conducted using purposive sampling, which produces 70 listed companies' samples during the years of observation. The analytical method of this study uses multiple regression analysis of Econometric views 8. This research study concludes that partial testing shows that firm size, audit committees and board size are positively and significantly related to risk management disclosure. Profitability, leverage, liquidity have no significant influence on risk management disclosure. Hypothesis testing uses multiple linear regressions. Data are obtained using Eviews version 8 software application. Data analysis model done with multiple regression model aiming to examine the influence of audit committee size, board of commissioner size, firm size, profitability, and leverage toward risk management disclosure Based on the research study result that has been analyzed statistically using multiple linear regressions, it can be concluded that variables of firm size, leverage, audit committee, and board of commissioner size positively and significantly affect corporate risk management disclosure. Meanwhile, variables of profitability, liquidity, and public ownership do not positively and significantly affect risk management disclosure.
Keywords: M49; 330; risk management disclosure; company characteristics; good corporate governance; audit committee; board size and public ownership structure; index enterprise risk management